Os alunos do 1º ano do ensino médio e os padrões: observação, realização e compreensão - Ferreira, Cristiane Regina de Moura (2009)
The present study relates a qualitative research that aims to investigate as the student, which one was concluded the 2008 High School first year, observes, realizes and understands the activities observation of regularities and generalization of patterns. This research relevance justifies itself for the subject importance Observation of Regularities and Generalization of Patterns , pointed for researchers as Stenn (1990), Orton and Orton (1999), Vale and Pimentel (2005) and Valle et al (2005), where they affirm that this resource assists the student to learn a relevant mathematics, besides revealing his algebraic comprehension. For the data collection I elaborated and I applied a diagnostic technique, inspired in the Didactic Engineering ideas, as seen in Machado (2003). The data analyses indicate that students realize pertinent observations to the regularities in the sequences and realize some generalizations of patterns, using different resolution strategies and types of semiotics representation (Duval, 2003). With regard to the understanding I can affirm that the pupils if find in development phase, therefore still need other experiences, to perfect the algebraic fluency and to reveal its thought algebraic in more efficient way